Predictive expressions for withdrawal force capacity of various size of dowels from particleboard and medium density fiberboard - Yüksel, Mehmet; Kılıç, Halil; Kuşkun, Tolga; Kasal, Ali (Maderas. Ciencia y Tecnología, 2022)
The objective of this study was to develop predictive expressions for estimating the withdrawal force capacity of various size of beech (Fagus orientalis) dowels from medium density fiberboard (MDF) and particleboard (PB). Furthermore, effects of the base material type, dowel diameter, dowel penetration and adhesive type on withdrawal force capacity were investigated. Polyurethane (PU), polyvinyl acetate based D2, and polyvinyl acetate (PVA) adhesives were utilized for gluing of dowels. A total of 540 specimens were prepared for edge and face withdrawal force capacity tests including two material types (MDF, PB), three dowel diameters (6 mm, 8 mm, 10 mm), three dowel penetration depths (15 mm, 20 mm, 25 mm for edge, 6 mm, 9 mm, 12 mm for face), three adhesive types and five replications for each group. Specimens were tested under static withdrawal forces. Based on results of tests, predictive expressions that allow furniture engineers to estimate edge and face dowel withdrawal force capacity as a function of dowel diameter and dowel penetration were developed. Calculations showed that the expressions developed provided reasonable estimates for withdrawal force capacity of dowels. As a result of statistical analyses, material type, dowel diameter, dowel penetration, adhesive type and their four-way interaction have significantly affected the withdrawal force capacity of dowels. Test results also indicated that PU adhesive and MDF ranked the highest withdrawal force capacity among the adhesive and material types. Increasing either dowel diameter or penetration tended to have a positive effect on withdrawal force capacity. Dowel diameter was found to have a higher effect on withdrawal force capacity than dowel penetration.